PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DALAM PENGGUNAAN JASA O.R 44 HOTEL PAGAR DEWA KOTA BENGKULU - Harsono, Gindy; Rindawati , Septi; Hartono, Rudi (Jurnal Adminitrasi Bisnis Nusantara, 2024)
The problem presented in this research is how does service quality influence consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City? How much influence does service quality have on consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City? The purpose of this research is to determine the influence of service quality on consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City, to find out how much influence service quality has on consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City. Sampling in this study used a technique using accidental sampling, namely a technique that complies with the researchers' criteria, namely that they are consumers using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City with a sample size of 40 people. Data collection methods include observation, documentation, literature and questionnaires. Data analysis techniques include validity and reliability tests, descriptive analysis, and classical assumption tests. The research results showed that service quality has a significant effect on consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City. From the results of calculations using the Determination formula, it is obtained that the level of influence of service quality on consumer satisfaction in using the services of O.R 44 Hotel Pagar Dewa, Bengkulu City is 81.6%